RETRACTED: Beyond Islamophobia: Unpacking Economic Motivations in South Korea’s Mosque Construction Debates - Yi, Soojeong; Koo, Gi Yeon (Indonesian Journal of Islam and Muslim Societies, 2025)
Retraction notice to ‘Beyond Islamophobia: Unpacking Economic Motivations in South Korea’s Mosque Construction Debates’ (Indonesian Journal of Islam and Muslim Societies, 15 (1), 109-141) This article has been retracted at the request of the Authors. The authors approached the journal after publication to alert the journal that their paper addresses a sensitive issue. They claimed that the parties involved in the conflict have formally expressed strong dissatisfaction with the content. Without the agreement of the parties involved in the research, the editors have agreed to retract it. The journal has removed this document and its contents. All existing references to this article should now be deleted. DOI of original article: https://doi.org/10.18326/ijims.v15i1.109-141 Keywords: Muslim in Korea, Islam, Mosque in Korea, migrant Muslims, Islamophobia